Identification of N-benzylacetamide as a major component of human plasmatic metabolic profiling of benznidazole - Marson, María Elena (2015)
Chagas disease is an endemic infection in Latin America with a high health impact. Caused by the parasite Trypanosoma cruzi, it has expanded to non-endemic regions such as North America and European countries via immigration of infected people. This infectious disease has been rising in the ranking of international health priorities due to the growing migration flows from endemic to non-endemic areas. Benznidazole (BZN), a nitroheterocyclic drug, is one of the two trypanocidal drugs currently in clinical use, associated with significant adverse drug reactions (ADRs). Mammalian metabolism of BNZ has been poorly studied, including the potential role of metabolites on both toxicity and anti-parasitic activity. High-resolution UPLC/MS/MS was used to analyze three plasma samples obtained from pediatric patients under BNZ treatment in steady state. Spectroscopic and structural criteria were applied to identify BNZ and accompanying substances from chromatographic signals. From all detected species, two can be undoubtedly associated with the BNZ and N-benzylacetamide molecules, the second one being a fragment of the parent drug (BZN). From the obtained results, two hypotheses could be formulated. The first one is to relate the presence of N-benzyl acetamide with the hepatic metabolism of BNZ. The second hypothesis has to do with the possible trypanocidal activity of this metabolite, as well as its role in the development of side effects, associated with the pharmacotherapy. Complementary studies should be carried out to determine the possible association of this metabolite with the BNZ treatment stages, patient's clinical features, ADRs, and trypanocidal effectiveness.